A Ferritin-Based Eg95 Nanoparticle Vaccine Adjuvanted with pCpG Eliciting Robust Immune Responses Against Cystic Echinococcosis in Mice Model - Gao X; Zhu X; Liu X; Zhou C; Shang Y; Wu T; Jia H; Zhang Z; Li Y; Xin T (International Journal of Nanomedicine)
Xintao Gao,1,* Xizhou Zhu,2,* Xingjian Liu,1 Chenghao Zhou,1 Yuting Shang,1 Tong Wu,1 Hong Jia,3 Zhifang Zhang,1 Yinü Li,1 Ting Xin3 1National Key Laboratory of Agricultural Microbiology, Biotechnology Research Institute, Chinese Academy of Agricultural Sciences, Beijing, People’s Republic of China; 2Bioproducts Engineering Center, Chinese Academy of Agricultural Sciences, Beijing, People’s Republic of China; 3Institute of Animal Sciences, Chinese Academy of Agricultural Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ting Xin; Yinü Li, Email xinting@caas.cn; liyinv@caas.cnIntroduction: Cystic echinococcosis (CE), a chronic disabling parasitic zoonosis, poses a great threat to public health and livestock production and causes huge economic losses globally. The commercial Quil-A-adjuvanted Eg95 vaccine was empirically effective for CE control; however, it is expensive and has side effects and insufficient immunity.Purpose: This study aimed to employ a novel adjuvant consisting of a delivery system and an immune potentiator and assess its adjuvanticity to Eg95 antigen, thereby developing a safe and cost-effective novel vaccine against the disease.Methods: A ferritin-based Eg95 nanoparticle antigen was prepared and then mixed with a plasmid containing the TLR9 agonist CpG to formulate a novel nanovaccine. The safety and efficacy of the vaccine were evaluated in vitro and in vivo.Results: The nanovaccine induced potent and enduring Eg95-specific humoral and cellular immune responses, as well as protective immunity-associated Th1 polarization supported by the higher ratios of IgG2a/IgG1 and IFN-γ/IL-4. Meanwhile, this nanovaccines exhibited favorable safety and economic profiles.Conclusion: Our data demonstrated that the ferritin-CpG hybrid is a promising combination adjuvant to upgrade the traditional Quil-A and this combination adjuvant-based nanovaccine presents good potential as an alternative to the commercial one for practical CE control. Keywords: cystic echinococcosis, vaccine, combination adjuvant, ferritin nanoparticle, CpG